Evaluation of Quality Management System for an Alcoholic Beverage Industry - Quaye, Joseph (2018)
A thesis submitted to the Department of Food Science and Technology, College of Science, in partial fulfilment of the requirements for the degree of Master of Science in Food Quality Management,